Tingkat kepadatan populasi Alona sp. pada media tumbuh ragi - Pangkey, Henneke; Lantu, Sartje; Silooy, Fanny (Universitas Sam Ratulangi, 2021)
The purpose of this research was to investigate the population density of Alona sp. on yeast media with different concentrations. The study was conducted using a completely randomized design (CRD) consisting of 5 treatments and 3 replications for 21 days. The treatments given were A: 10 ppm yeast, B: 5 ppm yeast, C: 1 ppm yeast, D: horse manure, and E: well water. The initial stocking density of Alona sp. for each treatment was 15 individuals/300 mL of well water. The water quality parameter measured during the study was temperature. The results of the one-way ANOVA test showed that there were significant differences between treatments on the density level of Alona sp. (p <0.05). Tukey's further test showed that treatment B was the best with a density of Alona sp. as many as 8059 individuals/300 mL of well water. The temperature during the study, in the morning was 26 ± 0.52°C and in the afternoon was 26 ± 0.46°C.